2003
DOI: 10.1089/154065803770381075
|View full text |Cite
|
Sign up to set email alerts
|

Drug Targets in the Voltage-Gated Calcium Channel Family: Why Some Are and Some Are Not

Abstract: The L-type calcium channel antagonists have been, and continue to be, a very successful group of therapeutic agents targeted at cardiovascular disorders, notably angina and hypertension. The discovery that the voltage-gated calcium channels are a large and widely distributed family with important roles in both the peripheral and central nervous systems has initiated a major search for drugs active at other calcium channel types directed at disorders of the central nervous system, including pain, epilepsy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 184 publications
(174 reference statements)
2
22
2
Order By: Relevance
“…We also observed that verapamil and dipyridamole significantly impaired ATP release, which implicates ABC and nucleoside transporters. However, verapamil acts on other targets including L-type Ca 2+ channels (36). These latter results are in contrast to those of a previous study that found no effect of verapamil or dipyridamole on ATP release from guinea pig ureter epithelium (7) and may reflect species differences or differences in ureter versus bladder epithelium.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We also observed that verapamil and dipyridamole significantly impaired ATP release, which implicates ABC and nucleoside transporters. However, verapamil acts on other targets including L-type Ca 2+ channels (36). These latter results are in contrast to those of a previous study that found no effect of verapamil or dipyridamole on ATP release from guinea pig ureter epithelium (7) and may reflect species differences or differences in ureter versus bladder epithelium.…”
Section: Discussioncontrasting
confidence: 90%
“…Glibenclamide, a blocker of some ion ABC proteins such as the CFTR and sulfonylurea receptors (33,34), had no significant effect on serosal ATP release but did cause a decrease in mucosal ATP release (Figure 1, A and B). Verapamil, an inhibitor of several additional ABC proteins (35) and L-type Ca 2+ channels (36), and dipyridamole, an inhibitor of nucleoside transporters (37), caused significant inhibition of both serosal and mucosal ATP release ( Figure 1, A and B). No ATP release was observed when the uroepithelium was first removed by gentle scraping before the underlying submucosa was mounted and exposed to pressure (Figure 1, A and B), which confirms that the uroepithelium was the source Figure 1 ATP localization, release, and hydrolysis in uroepithelium.…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, verapamil, which binds to the site of phenylalkilamines and does not affect the DHPR inactivation process, was without effect (31). An increase in spark frequency was found with a DHPR agonist (BayK) that interacts with the dihydropyridine site (50,51) and also with FPL, which appears to have a different mechanism of action and involves binding to a novel benzolpyrrole site (50). We did not test all other available classes of DHPR modulators.…”
Section: Discussionmentioning
confidence: 99%
“…In intact cells, direct effects of nifedipine on Ca 2ϩ sparks were not found; however, nifedipine inhibited the action of BayK (23,44). The differential effect of nifedipine may be related to the preferred binding of this compound to the open or inactivated conformations of the DHPR, which are favored when the membrane potential collapses (as in permeabilized cells) (22,31,50,51). At Ϫ80 mV (as in intact cells), DHPR channels are mostly in the closed state, which has a much lower affinity for nifedipine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation